Sistem Pendukung Keputusan Pemilihan Employee of The Month Menggunakan Metode SAW Pada PCJL Jambi - Najuantah, Putra; Roestam, Rusdianto (Jurnal Manajemen Sistem Informasi, 2023)
Employee of The Month is a program for best employee selection based on HSE criteria on PCJL – Jambi, most of the process performed manually which spending a lot of time to complete. Author conducted research as an effort to solve the problem by analyzing and designing a prototype of Decision Support System (DSS) utilized Simple Additive Weighting (SAW) method. Expected, by the design of this system will be a useful solution for the process and shorten the implementation time of the program.